Carbimazole-Induced Severe Acquired Aplastic Anemia in a Patient with Graves’ Disease: A Case Report - Rahaf A. Alghamdi; Hind A. Alshankiti; Adel F. Al-Marzouki; Yara M. Daous (Reports, 2026)
Background and Clinical Significance: Carbimazole is a widely used medication to treat Graves’ disease, although it can rarely cause acquired aplastic anemia, a complication that happens in less than 0.01% of people. Case Presentation: We report a 36-year-old woman treated with supratherapeutic dose carbimazole who, after approximately six months of treatment, developed high grade fever, severe menorrhagia, spontaneous epistaxis, and pancytopenia. Her bone marrow biopsy showed severe bone marrow failure with only 5% cellularity and trilineage hypoplasia. Other potential causes were ruled out. Immediate discontinuation of carbimazole was done, and supportive care, including blood transfusions, broad-spectrum antibiotics, G-CSF, and eltrombopag, was started. The patient deteriorated during her hospital stay, developed neutropenic sepsis and acute respiratory failure from diffuse alveolar hemorrhage, which required intubation and pulse steroid therapy. She was stabilized and discharged, with a referral to a tertiary medical center for starting antithymocyte globulin (ATG) immunosuppressive therapy, which she subsequently completed; two months after discharge she was transfusion independent with near-normalization of her blood counts. Conclusions: This case serves as a stark reminder of how lethal thionamide-induced bone marrow failure can be, highlighting the vital need for immediate drug cessation, swift intensive care, and thorough patient education on early warning signs.